Kemampuan Pemasaran Produk Berbasis Media Sosial Dengan Model Problem Based Learning - Veri Aryanto Sopiansah; Dini Riani; Cep Miftah Khoerudin; Leni Maryani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2023)
The problem that often arises in relation to entrepreneurship is product marketing which is a very important aspect of running a business. Good product marketing skills can help to expand market share, increase sales, and improve brand image. 21st century learning is known as the 4Cs (critical thinking, communication, collaboration, and creativity) as four skills that are important and needed for 21st century education, especially in the learning planning process. This study raises the issue of efforts to use social media with the help of the Problem Based Learning model to improve product marketing learning outcomes in Craft and Entrepreneurship subjects. The research was conducted at Bumi Siliwangi High School Bandung - West Java in class XI IPS 1 and 2 as many as 36 people in each class. The implementation of this study used two classes where the IPS 1 class would apply Problem Based Learning and was said to be the experimental class and the IPS 2 class would apply lectures and was said to be the control class. Data collection instruments in the form of evaluation test sheets and observation sheets. Data analysis was carried out by analyzing learning outcomes which produced scores and average values. The results showed that there were differences in learning outcomes, teacher and student activities, the teacher's ability to manage learning, and good student responses to the application of the Problem Based Learning model with social media which was more varied than the non-experimental class.